Additives in Honey Detection: A Review Paper (International Journal of Innovative Research in Computer Science & Technology, 2020)
The adulterant of choice for my sample is  sugar cane and corn syrup, which is one of the most  frequent adulterants used in a range of honey products.  Honey adulteration is a complex issue across the world in  general and in our country in particular, according to most  studies, and it has a major economic impact. It may be  induced by the introduction of various cheap foreign  substances. Contamination of honey changes the  physiochemical besides rheology of honey, reducing its  nutritional and therapeutic qualities. As a result,  techniques of adulterate detection and precise  measurement of adulterants would have been used to  produce high quality honey devoid of any foreign addition.  Numerous approaches used for honey adulteration  detection by maximum researchers, such as, Liquid  Chromatography (LC) and Gas Chromatography (GC)  analysis, protein characterization, Near Infra-Red (NIR)  spectroscopy, Fourier Transform Infrared (FTIR)  spectroscopy with Attenuated Total Reflectance (ATR),  High Performance Anion Exchange Chromatography with  Pulsed Aerometric Detection (HPAEC-PAD), High  Performance Liquid Chromatography Coupled to Isotope  Ratio Mass Spectrometry (HPLCIRMS), calorimetric  methods, Stable Carbon Isotope Ratio Analysis (SCIRA),  Fourier Transform (FT), Raman spectroscopy and  microscopic detection techniques are appropriate as well  as deliver valuable knowledge. However, to obtain a full  besides reliable outcome, people ought not focus just on  each technique, but rather use a combination of them.
Keywords: Adulteration; Analysis; Food; Honey; Methods; Sugar; Syrup.